1999
DOI: 10.1111/j.1532-5415.1999.tb05208.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coexistence of Coronary Artery Disease, Ischemic Stroke, and Peripheral Arterial Disease in Older Persons, Mean Age 80 Years, in an Academic Hospital‐Based Geriatrics Practice

Abstract: These data showed that if CAD was present, ischemic stroke was also present in 32% and PAD in 26% of the population. If ischemic stroke was present, CAD was also present in 56% and PAD in 28% of the population. If PAD was present, CAD was also present in 68% and ischemic stroke in 42% of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
11

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(133 citation statements)
references
References 10 publications
4
118
0
11
Order By: Relevance
“…Leng et al also showed that patients with asymptomatic PAOD appear to have the same increased risk of cardiovascular events and death as symptomatic patients 20) . Therefore, identifying high-risk PAOD patients is due to concomitant coronary artery disease and cerebrovascular disease; these cardiovascular events are more frequent than ischemic limb events in such patients 17,18) . Criqui et al reported mortality rates in patients with PAOD after a 10-year follow-up period.…”
Section: Incidence Of Paod In Taiwanmentioning
confidence: 99%
“…Leng et al also showed that patients with asymptomatic PAOD appear to have the same increased risk of cardiovascular events and death as symptomatic patients 20) . Therefore, identifying high-risk PAOD patients is due to concomitant coronary artery disease and cerebrovascular disease; these cardiovascular events are more frequent than ischemic limb events in such patients 17,18) . Criqui et al reported mortality rates in patients with PAOD after a 10-year follow-up period.…”
Section: Incidence Of Paod In Taiwanmentioning
confidence: 99%
“…[1][2][3][4] Previous studies reported that the prevalence of coronary artery disease (CAD) in patients with PAD is 46 to 71%. 5,6) In addition, coexistence of CAD is the most important determinant of mortality and longterm prognosis in patients with PAD 1,7,8) and patients with PAD had the same relative risk of death as those with a previous cardiovascular event.…”
Section: P Eripheral Artery Disease (Pad) Is Frequently Accompa-mentioning
confidence: 99%
“…17) Conversely, the frequencies of concurrence of CS in CAD and PAD patients have also been reported. 11,29) Kawarada et al 16) observed that CAD was complicated by CS in 13.7% and by PAD in 15.3% of the 380 patients who underwent elective CABG and reported the necessity of screening patients with cardiovascular risk factors for atherosclerotic diseases. 11) Marek et al 29) performed carotid artery ultrasound in 188 patients showing claudication with no history of cerebrovascular disorder and reported that ≥50% internal CS was noted in 24.5% and that it was occluded in 2.7%.…”
Section: Discussionmentioning
confidence: 99%
“…8,9) In actual clinical settings, we often encounter patients with CS complicated by other atherosclerotic diseases and those in whom CS is incidentally detected during the treatment for other atherosclerotic diseases such as CAD. 10,11) In revascularization for CS, CAD has been reported to be a risk factor for early as well as late death, 12) and PAD makes it difficult to perform CAS by the femoral approach and often limits devices and techniques that can be used. Thus, the concurrence of various atherosclerotic diseases affects the therapeutic strategy and outcomes of CS, but reports on the frequencies of CAD, PAD, and RAS as comorbidities of CS have been few.…”
Section: Introductionmentioning
confidence: 99%